CO2 Photoreduction: Heterostructure Engineering of a Reverse Water Gas Shift Photocatalyst (Adv. Sci. 22/2019). Issue 22 (20th November 2019) - Wang, Hong; Jia, Jia; Wang, Lu; Butler, Keith; Song, Rui; Casillas, Gilberto; He, Le; Kherani, Nazir P.; Perovic, Doug D.; Jing, Liqiang; Walsh, Aron; Dittmeyer, Roland; et al.
Abstract : In article number 1902170, Hong Wang, Geoffrey A. Ozin, and co‐workers present a hetero‐nanostructure, oxygen vacancy, electronic band alignment and carrier lifetime engineering strategy of In2 O3− x (OH) y @Nb2 O5, enabling the solar‐powered, reverse water gas shift reaction to operate at a 44‐fold higher conversion rate than pristine In2 O3− x (OH)y, with high selectivity and long‐term operational stability, an advance that augers well for the metal oxide hetero‐nanostructure engineering approach to the industrialization of gas‐phase CO2 photocatalysis. Image credit: Chenxi Qian.